Mobile Learning Based Android Multimedia Development on Basket Ball Learning for Junior School Graders (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purpose of the research is to findout the development of Android based multimedia learning in the form of Mobile Learning to teach health and sport course specifically basket ball for Junior School graders and to findout its effectiveness toward the material. This developmental research has procedures of product development covering analysis of created product, initial product development, expert validation and revision, small group trial run and revision, larger group trial run and final product. The data collection is done by using questionnaire, gained from expert evaluation, and using field observation gained from students. The technique of analysing the data is descriptive percentage. The final trial run test is gained average score of product analysis equals to 84.5%, categorized â€œwellâ€. The observation findings and questionnaires of the teachers gaines average score of product analysis equals to 83.2%, â€œwellâ€. And the findings of observation and questionnairs from students in small group trial run test gain percentage of average score equals to 86%, â€œvery wellâ€. And the findings of observation and questionnaires in larger sclase is gained the average score 87%, â€œwellâ€. From the findings can be concluded the resulted multimedia product in learning basket ball based android in form of application (apk) to be downloaded by teachers and studetns from Playstore thought keyword â€œBasket SMPâ€. Teacher and students in learning having more interest on the application. The product is effective to learn the material for Junior School graders in Tengaran district, Semarang.